2017
DOI: 10.1111/nmo.13044
|View full text |Cite
|
Sign up to set email alerts
|

Rectal gas volume: Defining cut‐offs for screening for evacuation disorders in patients with constipation

Abstract: Background Diagnosis of rectal evacuation disorders (RED) is currently based on anorectal manometry and evacuation tests in specialized laboratories; we recently showed higher rectal gas volume (RGV) and maximum rectal gas transaxial area (MRGTA) measured on abdominal and pelvic computed tomography (CT) in patients with documented RED. Aim To obtain cut-off values of RGV, MRGTA and rectal area on scout film (RASF) to differentiate constipated patients with RED from those without RED, based on anorectal manom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Park et al . demonstrated that rectal gas volume was a marker of defecatory disorders; at a specificity of 90%, a rectal gas volume of 30 mL had a PPV of 77.3% for an evacuation disorder 50 , 51 .…”
Section: Normal and Abnormal Colonic And Anal Structure And Functionmentioning
confidence: 99%
“…Park et al . demonstrated that rectal gas volume was a marker of defecatory disorders; at a specificity of 90%, a rectal gas volume of 30 mL had a PPV of 77.3% for an evacuation disorder 50 , 51 .…”
Section: Normal and Abnormal Colonic And Anal Structure And Functionmentioning
confidence: 99%
“…The method for measuring the rectal area of gas on scout film (RASF) of an abdominal computed tomography (CT) scan has been previously published and validated relative to the estimated rectal gas volume measured by the same CT scan after 3-dimensional reconstruction. 15,23 From our previous studies, we used mean RASF >9 cm 2 (92.3% specificity and 68.8% positive predictive value) as the cut-off to diagnose RED. 23…”
Section: Methodsmentioning
confidence: 99%
“…15,23 From our previous studies, we used mean RASF >9 cm 2 (92.3% specificity and 68.8% positive predictive value) as the cut-off to diagnose RED. 23…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations